Association between higher pericoronary adipose tissue attenuation measured by coronary computed tomography angiography and nonalcoholic fatty liver disease: A matched case-control study. Issue 34 (27th August 2021) - Ichikawa, Keishi; Miyoshi, Toru; Osawa, Kazuhiro; Miki, Takashi; Morimitsu, Yusuke; Akagi, Noriaki; Nakashima, Mitsutaka; Ito, Hiroshi
Abstract : Abstract: Non-alcoholic fatty liver disease (NAFLD) is a risk factor for cardiac mortality. Pericoronary adipose tissue (PCAT) attenuation, expressed by the fat attenuation index on coronary computed tomography angiography, reflects pericoronary inflammation. We aimed to investigate the association between PCAT attenuation and NAFLD. This is a single-center cohort study comprising of patients who underwent coronary computed tomography angiography for suspected stable coronary artery disease between January and December 2020. Patient characteristics and coronary computed tomography angiography findings were analyzed between patients with NAFLD (n = 78) and a propensity score-matched cohort of patients without NAFLD (n = 78). PCAT attenuation was assessed in Hounsfield units (HU) of proximal 40-mm segments of the left anterior descending artery (LAD) and right coronary artery. The mean PCAT attenuation in LAD and right coronary artery were significantly higher in patients with NAFLD than those without NAFLD. When patients were divided into 2 groups using the median LAD-PCAT attenuation of −72.5 HU, the high PCAT attenuation group had more males (82% vs 67%, P = .028) and NAFLD patients (63% vs 37%, P = .001) compared to the low PCAT attenuation group. No differences in age, body mass index, conventional cardiovascular risk factors, or the presence of high-risk plaque were observed between the 2 groups. In the multivariate logistic analysis, NAFLD was independently associated with high PCAT attenuation (odds ratio 2.912, 95% confidence interval 1.386 to 6.118, P = .005). NAFLD is associated with high PCAT attenuation on coronary computed tomography angiography. This finding suggests that pericoronary inflammation is involved in the increased cardiac mortality in NAFLD patients.